Genome archaeology of two laboratory Salmonella enterica enterica sv Typhimurium. Issue 9 (8th July 2021) - Zaworski, Julie; Dagva, Oyut; Kingston, Anthony W; Fomenkov, Alexey; Morgan, Richard D; Bossi, Lionello; Raleigh, Elisabeth A
Abstract: The Salmonella research community has used strains and bacteriophages over decades, exchanging useful new isolates among laboratories for the study of cell surface antigens, metabolic pathways and restriction-modification (RM) studies. Here we present the sequences of two laboratory Salmonella strains (STK005, an isolate of LB5000; and its descendant ER3625). In the ancestry of LB5000, segments of ∼15 and ∼42 kb were introduced from Salmonella enterica sv Abony 803 into S. enterica sv Typhimurium LT2, forming strain SD14; this strain is thus a hybrid of S. enterica isolates. Strains in the SD14 lineage were used to define flagellar antigens from the 1950s to the 1970s, and to define three RM systems from the 1960s to the 1980s. LB5000 was also used as a host in phage typing systems used by epidemiologists. In the age of cheaper and easier sequencing, this resource will provide access to the sequence that underlies the extensive literature.